Radiorientations and radioptions an analysis of the listenership, listening bahaviors and preferences in the consumption of radio by selected high school students in Quezon City - Moreno, Earl Marion R. 1990- (2012)
"The research aims to "put a face" on radio's high school audiences. This was achieved by determining high school students' listenership, listening behaviors, preferences when listening to radio, and the impact that socio-economic classes have on these variables. Using a quantitative approach, two theories were used by the researcher which encompasses listenership, behavior, and preferences - McQuail's Structural Model of Media Use and Everett's Digitextuality and Click Theory. A survey to examine the correlation of these variables and the socio-economic classes of high school students was conducted with Quezon City high schools - Angelicum College High School (ACHS) and Ramon Magsaysay (Cubao) High School (RMCHS). Statistical analysis was used to analyze the survey data and from these, it was concluded that approximately 50 percent from ACHS and 70 percent from RMCHS indicated that they regularly listen to the radio. Socio-economic class did not play a big role in affecting these variables. This implies that high school students still consider radio as a medium in their media consumption. A similar study of a wider scale, Metro Manila or even nationwide perhaps, and more refined methodologies would be recommended to see whether the same could be said for all Filipino high school students."
Vita.
Thesis (A. B. in Broadcast Communication)--University of the Philippines, Diliman.
Keywords: Radio audiences -- Philippines